2021
DOI: 10.1038/s41419-021-03624-9
|View full text |Cite
|
Sign up to set email alerts
|

ADCK1 activates the β-catenin/TCF signaling pathway to promote the growth and migration of colon cancer cells

Abstract: As a result of mutations in the upstream components of the Wnt/β-catenin signaling pathway, this cascade is abnormally activated in colon cancer. Hence, identifying the activation mechanism of this pathway is an urgent need for the treatment of colon cancer. Here, we found an increase in ADCK1 (AarF domain-containing kinase 1) expression in clinical specimens of colon cancer and animal models. Upregulation of ADCK1 expression promoted the colony formation and infiltration of cancer cells. Downregulation of ADC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The lentiviral particles encoding the ADCK1 shRNA (sequence listed in [ 16 ]), the ADCK2 shRNA, the ADCK3 shRNA, or the mTOR shRNA were obtained from GeneChem Inc. (Shanghai, China). According to the instruction, OS were plated into a six-well plate at 8.5 × 10 4 cells per well for 24 h. Cells were then infected with the virus at the multiplicity of infection (MOI) of 20.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The lentiviral particles encoding the ADCK1 shRNA (sequence listed in [ 16 ]), the ADCK2 shRNA, the ADCK3 shRNA, or the mTOR shRNA were obtained from GeneChem Inc. (Shanghai, China). According to the instruction, OS were plated into a six-well plate at 8.5 × 10 4 cells per well for 24 h. Cells were then infected with the virus at the multiplicity of infection (MOI) of 20.…”
Section: Methodsmentioning
confidence: 99%
“…It is not clear whether ADCK1 also affects the functions of mitochondria and behaviors of human cells, and whether its expression is altered in human cancer cells. A very recent study by Ji et al, reported that ADCK1 is overexpressed in clinical colon cancer specimens and involved in colon cancer tumorigenesis [ 16 ]. ADCK1 silencing, by the shRNA strategy, potently inhibited colon cancer cell colony formation and infiltration as well as the in vivo tumorigenesis, migration, and organoid formation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations